Study of Currency Risk and the Hedging Strategies - TIWARY, Anuradha R. (Journal of Advanced Studies in Finance; Vol 10 No 1 (2019): JASF Volume X Issue 1(19) Summer 2019DO - 10.14505//jasf.v10.1(19).05, 2019)
The globalization of financial markets achieved by dynamic technological advancements, financial market liberalization and the departure of capital controls have urged all MNC with foreign money streams the need to manage foreign exchange exposure risks introduced by a volatile exchange system. Today, multinational firms are striving to create methods and methodologies for an efficient and effective exchange risk management. The foreign exchange strategy embraced is essential to an MNC in the present-day condition because of the great inconstancy in transaction rates and needs to advance with the dynamic structure of the organization. Further, given the way that organizations are continually signing commercial and business contracts titled in foreign currencies, precise estimation and supervision of exposure and economic risks have turned out to be vital to the success of an MNC. This paper review the traditional types of exchange rate risks faced by the firms due to the surge of global quest for trade across borders. The paper further explains the importance of risk management strategies with special reference to hedging and outline the various hedging strategies both external and internal used by Multinational companies (MNC’s).